Recent Forest Cover Loss in the Core Zones of the Monarch Butterfly Biosphere Reserve in Mexico - Flores-Martínez, José Juan; Martínez-Pacheco, Anuar; Rendón-Salinas, Eduardo; Rickards, Jorge; Sarkar, Sahotra; Sánchez-Cordero, Víctor (Frontiers in Environmental Science, 2019)
The Monarch Butterfly Biosphere Reserve (MBBR) in central Mexico was established in 2000 to protect monarch butterfly (Danaus plexippus) overwintering colonies and contribute to the conservation of the monarch migratory phenomenon. Since it was decreed, the MBBR has faced deforestation pressures (forest cover loss) due to illegal logging and climatic factors. Here we report deforestation trends from 2012 to 2018 in the core zones of the MBBR where most monarch overwintering colonies perch. We used aerial ortho-photographs and satellite images complemented with field validation for temporal comparisons. During this period, 163.44 ha of forest cover were affected; 125.44 ha due to natural factors (rain and wind), 25.86 ha due to large-scale illegal logging, and 12.14 ha due to small-scale illegal logging. The core zone of the MBBR located in the State of Michoacán showed the highest deforestation values with 94.07 ha lost due to climatic factors, and 32.63 ha lost due to large-scale illegal logging. Over all illegal logging significantly decreased in the core zones of the MBBR due to an effective shared conservation effort including local communities, NGOs, academic institutions, governmental agencies, and philanthropists. Our study also showed a significant decrease of approximately 98% in large-scale illegal logging in the core zones of the MBBR compared to previous years from 2001 to 2012 (Vidal et al., 2013). Deforestation due to climatic factors remained similar (120 to 130 ha) between both studies. The decrease of deforestation during the period studied suggests that factors elsewhere rather than deforestation in the monarch butterfly’s winter habitat have strongly contributed to the dramatic population declines observed in recent years of monarch overwintering colonies since 2010.